The UN Sec urity Council facing the contemporary global balance of power - Mejía Mejía, Kenny Gustavo (Scientific journal of social studies, 2023)
The Security Council is the cornerstone of the international security architecture. This body of the United Nations system has the central mission of ensuring the “maintenance of international peace and security.” Since its creation, it reflected the balance of power in the post-war period, endowing the victors of the Second World War with the status of permanent members with the power of veto in Council decisions, which ensured them a lasting leading role in the international system. During more than seven decades after the creation of the Security Council, the world has experienced profound transformations, giving rise to emerging powers that increasingly occupy a more significant role on the international stage. Faced with these new realities, the Security Council has remained unchanged, despite the numerous demands for reforms made by many States. When analyzing the economic, demographic and military indicators of the permanent members (United States, China, Russia, United Kingdom and France) in comparison with the member countries of the so-called G-4 (Brazil, India, Japan and Germany) it can be determined that the contemporary balance of power is not fully reflected in the current structure of the Security Council. These emerging powers should acquire permanent member status to increase the Council’s legitimacy and its ability to effectively represent global interests.
Keywords: Security Council; balance of power; veto power; permanent members; international politics